The effects of endocannabinoid signaling on network activity in developing and motor circuits. (26th March 2013) - Wenner, Peter
Abstract : Endocannabinoid signaling typically mediates a form of synaptic plasticity in which a postsynaptic cell acts retrogradely to reduce vesicle release from presynaptic terminals impinging on that cell. In the embryonic spinal cord, endocannabinoids inhibit spontaneously released glutamatergic vesicles in both a brief and ongoing tonic manner. Together these endocannabinoid‐mediated forms of synaptic regulation appear to play an important role in regulating the frequency of a form of spontaneous network activity (SNA) that is expressed in the embryonic spinal cord. Because of the importance of SNA to the maturation of the developing network, fetal exposure to drugs that influence endocannabinoid signaling may have profound effects on spinal maturation. In this review, endocannabinoid signaling in the embryonic spinal cord is described and compared to signaling in the mature lamprey spinal cord as well as in the developing hippocampal network, which expresses a form of SNA.